Analisis Kolektibilitas Pada Pembiayaan Murabahah Bank Syariah Dalam Upaya Menekan Non Performing Financing - Siregar, Sonia Afna; Rahma, Tri Inda Fadhila; Syahbudi, Muhammad (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
This study aims to determine the collectibility of murabahah financing at Bank Syariah Indonesia KCP Sukaramai, Medan. This research was conducted at Bank Syariah Indonesia KCP Sukaramai, Medan. The research method used was qualitative with a phenomenological approach, because this approach allows researchers to understand and explore the subjective experiences of customers related to murabahah financing and how they experience and understand the collectibility process. Research data were obtained through in-depth interviews with five customers who were selected purposively, where this selection was made based on considerations of representing their experiences in using murabahah financing at the bank. Although the sample size was limited, these five customers provided views that were quite representative of the experiences and problems frequently faced by customers at Bank Syariah Indonesia KCP Sukaramai. The research results show that the murabahah financing collectibility system at BSI KCP Sukaramai complies with national Islamic banking guidelines with five collectibility categories and has implemented an Early Warning System (EWS) to detect potential problem financing. However, its implementation has not been optimal, particularly in the follow-up of risk identification results. Monitoring is carried out through visits and communication, but limited human resources and a lack of customer response are major obstacles. In terms of figures, collectibility decreased from 90.03% in January 2024 to 83.20% in April 2024, along with an increase in the Non-Performing Financing (NPF) ratio from 5.76% to 12.58%. However, improvements were seen in May–June 2024, when collectibility rose back to 92.90% and the NPF ratio decreased to 2.57%. External factors such as the decline in customer business after the pandemic also influenced the dynamics of financing collectibility.